2020
DOI: 10.1002/1348-9585.12168
|View full text |Cite
|
Sign up to set email alerts
|

Concerns, perceived impact, and preparedness of oral healthcare workers in their working environment during COVID-19 pandemic

Abstract: Objective The aim of the study was to evaluate the oral healthcare workers' concerns, perceived impact, and preparedness in COVID‐19 pandemic. Methods This cross‐sectional study was carried out at 10 different dental hospitals in Pakistan from March to June 2020. A 35 items valid and reliable questionnaire was used to assess the concerns, perceived impact, and preparedness of oral healthcare workers (OHCW) in COVID‐19 pandemic. Chi‐squared test and logistic regression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 18 publications
2
48
0
5
Order By: Relevance
“…This study reports that a higher percentage of clinical DHCPs were afraid of falling ill with COVID-19 than non-clinical workers. Our finding is in line with other studies on HCWs in Singapore during the Avian Influenza outbreak and oral healthcare workers in Pakistan (Wong et al, 2008;Chaudhary et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study reports that a higher percentage of clinical DHCPs were afraid of falling ill with COVID-19 than non-clinical workers. Our finding is in line with other studies on HCWs in Singapore during the Avian Influenza outbreak and oral healthcare workers in Pakistan (Wong et al, 2008;Chaudhary et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…A small number of DHCPs (7.4%) reported that they would look for another job. The response is consistent with other studies conducted in Singapore, the USA, and Pakistan, where most healthcare workers agreed to continue work during SARS, Avian influenza, and COVID-19 outbreak respectively (Chaudhary et al, 2020;Wong et al, 2008;Martin, 2011). In contrast, other studies reported a higher proportion of healthcare workers from Taiwan, Hong Kong, and the United Kingdom (43%-77%) refused to work during an outbreak and preferred to look for another job or quit their job (Chaudhary et al, 2020;Wong et al, 2010;Shiao et al, 2007;Barr et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Dental health personnel are thus at high risk of contagion when performing routine dental procedures, and the dental office may serve as a cross-infection location if adequate precautions are not taken. In addition, as individuals with COVID-19 may be asymptomatic for several days, they pose a risk to the dental health personnel when seeking dental treatment [ 6 ]. The role of dental professionals in preventing transmission of SARS-CoV-2 is therefore critically important [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this challenging scenario, health professionals have faced drastic changes in their clinical routines, including enacting strict practices against cross‐infection, enhancing the management of minimally invasive procedures that generate less aerosols, reducing the number of patient visits (Jamal et al, 2020), and developing protocols for teleodontology services (Maret et al, 2020). Recent studies have indicated that the COVID‐19 pandemic has had not only negative economic consequences (Ali et al, 2020; Nibali et al, 2020; Schwendicke et al, 2020) but also increased the levels of fear and anxiety among the dental workforce (Ahmed et al, 2020; Chaudhary et al, 2020; Sharma et al, 2020). In this context, periodontists have been forced to adapt their clinical practice in various ways to reduce the transmission of SARS‐CoV‐2 while, at the same time, figuring out how to manage the emotional and financial impacts related to their new professional routine.…”
Section: Introductionmentioning
confidence: 99%